Association between pro-inflammatory diet and ulcerative colitis: a systematic review and meta-analysis - Yin, Xianli; Tian, Lv; Liu, Qi; Zhao, Hanbing (Frontiers in Nutrition, 2025)
BackgroundEmerging evidence suggests that dietary patterns can mediate intestinal inflammatory responses through immune-microbiome interactions. Diet and inflammation are important pathogenic factors for ulcerative colitis (UC). However, the existing evidence regarding the association between a pro-inflammatory diet and the risk of UC is controversial, and further clarification of this association is needed.ObjectiveThis study aimed to explore the association between pro-inflammatory diet and UC risk.MethodsWe systematically searched PubMed, Web of Science, Scopus, EMBASE, and Cochrane Library databases from their inception to January 15th, 2025. Two researchers independently used the Newcastle - Ottawa Scale to assess the quality of the included studies. Data analysis was performed using STATA 17 software.ResultsThis systematic review and meta-analysis included eight studies involving approximately 758,068 participants. The meta-analysis indicated that an inflammatory or pro-inflammatory diet did not increase the risk of UC (OR = 0.97, 95% CI = 0.84–1.12). However, subgroup analyses revealed differing results: within the case–control study subgroup, a pro-inflammatory diet was associated with an increased risk of UC (OR = 2.09, 95% CI: 1.23–3.56), whereas in the cohort study subgroup, no significant association was found between a pro-inflammatory diet and UC (OR = 0.91, 95% CI: 0.78–1.06). Sensitivity analysis indicated that the study results were robust. Additionally, Begg’s test (p = 0.174) and Egger’s test (p = 0.085) showed no significant publication bias in this study.ConclusionThe results of this study do not support a significant association between pro-inflammatory diets and UC risk. However, due to the limited level of evidence from observational studies and their heterogeneity, the association between pro-inflammatory diets and UC may be underestimated or overestimated. Therefore, larger multi-centre studies are needed to standardize the assessment of diets and adjust for microbial-related confounding factors in order to elucidate the association and mechanisms between pro-inflammatory diets and UC.